2019
DOI: 10.3390/cells8020131
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of NFATc1-Knockdown in RAW 264.7 Cells: An Alternative Pathway for Macrophage Differentiation

Abstract: NFATc1, which is ubiquitous in many cell types, is the master regulator of osteoclastogenesis. However, the molecular mechanisms by which NFATc1 drives its transcriptional program to produce osteoclasts from macrophages (M) remains poorly understood. We performed quantitative PCR (QPCR) arrays and bioinformatic analyses to discover new direct and indirect NFATc1 targets. The results revealed that NFATc1 significantly modified the expression of 55 genes in untransfected cells and 31 genes after NFATc1-knockdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…The remarkable upregulation of NFATc1 mRNA observed in RAW 264.7 cells since the 1st day after RANKL stimulation is a hallmark aspect of osteoclastogenesis. By our previous qPCR and bioinformatic analyses, we found that NFATc1 significantly influences the expression of 31 genes, which are differently involved in osteoclastogenesis [ 9 ]. A variety of data in literature support the idea that the initial induction of NFATc1 protein depends upon the cooperation of NFATc2 and NF-κB (in particular, components p50 and p65, named RelA ), both recruited to the NFATc1 promoter at the very early phase of OC differentiation, i.e., 1 h after RANKL stimulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The remarkable upregulation of NFATc1 mRNA observed in RAW 264.7 cells since the 1st day after RANKL stimulation is a hallmark aspect of osteoclastogenesis. By our previous qPCR and bioinformatic analyses, we found that NFATc1 significantly influences the expression of 31 genes, which are differently involved in osteoclastogenesis [ 9 ]. A variety of data in literature support the idea that the initial induction of NFATc1 protein depends upon the cooperation of NFATc2 and NF-κB (in particular, components p50 and p65, named RelA ), both recruited to the NFATc1 promoter at the very early phase of OC differentiation, i.e., 1 h after RANKL stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the expression of DC-STAMP mRNA is upregulated from the 1st day of RANKL stimulation, we can hypothesize that RANKL-induced DC-STAMP expression is necessary to restore it on the surface of differentiating OCs as a response to its previous internalization, which is in agreement with data reported in literature [ 30 ]. The mRNA expression levels of DC-STAMP and NFATc1 peaked at the same time points after RANKL stimulation and NFATc1-knockdown significantly inhibited DC-STAMP expression [ 9 ]. Several results suggest that there is a mutual regulation between DC-STAMP and NFATc1 at both gene and protein expression levels [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…M-CSF mainly promotes cellular proliferation, acting through ERK1/2-activation, whereas RANKL induces a switch versus differentiation [ 16 ]. It has been reported that RANKL, but not M-CSF, also induced a delayed (24 h) activation of p38 MAPKs that coincided with the initiation of OCs differentiation [ 16 , 17 ]. In particular, the axis RANKL-RANK-TRAF6-p38 MAP kinase promotes the expression of osteoclastogenic transcription factors, including NFATc1 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…We further investigated the molecular mechanisms by which RANKL-induced osteoclastogenesis is increased by isorhamnetin 3-O-neohesperidoside. NFATc1 is a master transcription factor that regulates osteoclastogenesis 21,22 ; NFATc1-deficient osteoclast precursor cells failed to differentiate into osteoclasts in response to RANKL stimulation, while NFATc1 caused precursor cells to undergo efficient osteoclast differentiation without RANKL signalling 21,23,24 . Western blotting showed that the expression of NFATc1 increased gradually from day 1 to day 5 after RANKL induction.…”
Section: Discussionmentioning
confidence: 99%